O Programa Nacional de Alimentação Escolar (PNAE) na perspectiva dos usuários: um estudo de caso - Costa, Liliam Magda Campos (2004)
The School Feeding National Program (PNAE) aims to contribute to overcome the low school revenue and in the reduction of the school escape. In spite of the social politics of school feeding not to seek to eliminate the child malnutrition in Brazil, just looking for to supply 15% of the children's needs daily, it is important for the fact of representing access to necessary foods to the growth and the learning for the scholars, as well as for supplying the possibility of the ransom of customs and local customs, important in the ethnic identity of the population. Besides, the resources destined to the purchase of the school snack can represent for the community a possibility of maintainable development, because the administration of the resources of a participant form can take to the construction of a new rationality in the exploration of the local natural resources. The main motivation of this work is to contribute for the discussions of the public politics in the reduction of the poverty and to understand the inter relationships among the offer of a compensatory politics and the impact s generated for the population plaintiff. It is looked for through a case study, where the geograp hical space is the municipal district of Tauá- CE, to determine the efficiency, effectiveness and effectiveness of a re-distribution program through the descriptive analysis of the PNAE users perspective. It is a subsequent evaluation, that if using of bibliographical and documental research , of the application of questionnaires to the school community, of interviews to the nutritionist and representatives of the institutions of local fomentation and of tabulation for the statistical program Statistical Package for the Social Sciences (SPSS), it evidences that the problems of infrastructure of the transports and highways of the municipal district and the absence of equipments in the schools represent the main impediments within reach of the effectiveness of the Program and that the loss of the purchase power of the R$ 0,13 per capita/day allied to the accomplishment of the equality of the population-objective made of a centralized form, commits its efficiency. Finally, it explicits the absence of the use of indicators for the measuration of its effectiveness by the managers of the program and the school community's ignorance in relation to its administration.